Modern Economic and Geographical Characteristics and Prospects of Development of Environmental Protection Infrastructure in the Baikal Region of Russia - Zabortseva, Tatiana (Quaestiones Geographicae, 2011)
In the administrative division of Russia, the Baikal region is traditionally considered as embracing three parts: the Irkutsk oblast', the Republic of Buryatia, and Zabaikalsky Kray. Its area is three times larger than that of France (1.6 million km2), but its population size and density are typical of "the Siberian depth of the country" (4.6 million people, under 3 persons/km2). One of the most important global features of a part of this region - the Baikal Natural Territory - is to ensure the preservation of Lake Baikal as a World Heritage Site. A strategy of environmentally oriented land use determines an adequate level of development of ecological infrastructure and its most important sector - environmental protection infrastructure (EPI). The article presents an analysis of the current infrastructure for managing solid waste, and proposes a forecast scenario of its development with the use of the gravity model in the EPI sector involving recycling collection points.